ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) TERHADAP LAPORAN KEUANGAN (Studi Kasus UD. Dwi Putra Surabaya) - Robiah, Lailatul; Amiranto, Jianto B. (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTThe financial report is a tool for analyzing the financial performance of companies that can provide information about the financial position, performance an clash flow, so it can serve as a basis for decision making by management. This study to describe the condition of the financial statements and describes the making SAK ETAP to the financial statements textile company Dwi Putra. This study used descriptive qualitative method with primary and secondary data sources and Data collection was done by means of interviews, documentation and observation. The study research are that the financial statements Dwi Putra consist of the balance sheet and income statements, where it does not conform to the presentation SAK ETAP, the accounting cycle of the company is also not in accordance with SAK ETAP. SAK ETAP does not stipulate rules of writing format or order against the post presented. Therefore, the presentation of the balance sheet and income statement Dwi Putra is not at issue in financial accounting standards entities without public accountability (SAK ETAP). Keywords : Financial Statements,SAK ETAP